Spin texture and chiral coupling of circularly polarized dipole field - Shi Yu; Kim Hong Koo (Nanophotonics)
We show that a circularly polarized electric dipole harbors a near-field concentrated wave which orbits around with an energy flux significantly larger (five orders of magnitudes at ∼1 nm radial distance) than far-field radiation. This near-field wave is found to carry transverse spins and reveal skyrmion spin texture (Néel-type). By performing electromagnetic analysis and numerical simulation, we demonstrate chiral extraction of a near-field rotational energy flux: the confined energy flow is out-coupled to surface plasmons on metal surface, whose curvature is designed to provide orbital angular momentum matched to spin angular momentum of dipole field, that is, to facilitate spin–orbit interaction. Strong coupling occurs with high chiral selectivity (∼113) and Purcell enhancement (∼17) when both linear and angular momenta are matched between dipole field and surface plasmons. Existence of a high-intensity energy flux in the deep-bottom near-field region (r ∼ 1 nm) opens up an interesting avenue in altering fundamental properties of dipole emission. For example, extracting ∼1% of this flux would result in enhancing spontaneous emission rate by ∼1000 times.